Incidence and remission rates of self‐reported hidradenitis suppurativa ‐ A prospective cohort study conducted in Danish blood donors. (23rd December 2021) - Kjærsgaard Andersen, R.; Loft, I.C.; Hansen, T.; Hjalgrim, H.; Rostgaard, K.; Banasik, K.; Bruun, M.; Nielsen, K.; Dinh, K.M.; Sørensen, E.; Burgdorff, K.; Erikstrup, C.; et al.
Abstract: Background: A large discrepancy between physician‐diagnosed and self‐reported Hidradenitis suppurativa (HS) exists. Knowledge regarding incidence and remission rates of self‐reported HS is missing, but may help bridge the gap in understanding between these two phenotypes. Objectives: To determine the incidence and remission rates of self‐reported HS, and to what degree these are affected by sex, smoking and BMI. Methods: A prospective cohort of 23 930 Danish blood donors. Information on self‐reported HS, symptom‐localisation, sex, age, BMI and smoking status was collected at baseline and study termination. Self‐reported HS fulfilled clinical obligatory diagnostic criteria. Cox proportional hazards regression analyses were conducted for both incidence and remission rates providing a hazard ratio (HR) of risk for each variable in the regression. Results: Incidence rate of self‐reported HS was 10.8/1000 person‐years (95% confidence interval (CI): 9.9–11.7), decreasing as a function of numbers of areas affected. Female BMI points above 25 (HR = 1.11, 95% CI: 1.09–1.13), male BMI points above 25 (HR = 1.07, 95% CI: 1.04–1.11), active smoking (HR = 1.72, 95% CI: 1.15–2.57), male sex (HR = 0.55, 95% CI: 0.45–0.67) and years of age above 25 (HR = 0.97, 95% CI: 0.96–0.97) were all statistically associated with the development of self‐reported HS. Remission rate of self‐reported HS was 256.7/1000 person‐years (95% CI: 223.9–292.6), decreasing as a function of numbers of affected areas. Symptoms in ≥3 areas (HR = 0.54, 95% CI: 0.34–0.85), active smoking (HR = 0.49, 95% CI: 0.32–0.76) and female weight loss (every percentage drop in BMI: HR = 1.07, 95% CI: 1.05–1.11) all significantly affected the remission rate. Conclusions: Both incidence and remission rates of self‐reported HS are high, indicating that many with self‐reported HS are unlikely to be diagnosed, as they to a higher degree experience mild transient HS symptoms.